The Scientist, the Artefact and the Exegesis: Challenging the parameters of the PhD - Tara Brabazon; Jamie Quinton; Narelle Hunter (IJCAS (International Journal of Creative and Arts Studies), 2022)
A PhD in science demands rigour, repeatability, and accountability. Epistemological, methodological, and ontological expectations flood the policies, procedures, and practice. One mode of doctorate has existed beyond the typical parameters of science: the artefact and exegesis PhD. Most commonly positioned in the creative arts and creative writing, how could this mode of doctorate be deployed in the sciences? This article, written by three academics who shared this innovative supervisory space, reveals the strengths and challenges that emerge from this innovative form and content for research. Our goal is to open out transformative spaces for doctoral education through diverse disciplines. Ilmuwan, Artefak, dan Eksegesis: Menantang Parameter PhDAbstrakGelar PhD dalam sains menuntut ketelitian, pengulangan, dan akuntabilitas. Harapan epistemologis, metodologis, dan ontologis membanjiri kebijakan, prosedur, dan praktik. Satu mode doktor telah ada di luar parameter khas sains: artefak dan eksegesis PhD. Paling sering diposisikan dalam seni kreatif dan penulisan kreatif, bagaimana mode doktor ini dapat digunakan dalam sains? Artikel yang ditulis oleh tiga akademisi yang berbagi ruang pengawasan inovatif ini mengungkapkan kekuatan dan tantangan yang muncul dari bentuk dan konten inovatif untuk penelitian ini. Tujuan kami adalah untuk membuka ruang transformatif untuk pendidikan doktoral melalui beragam disiplin ilmu.